The ANALYSIS OF A SOLAR POWER GENERATION SYSTEM (International Journal of Engineering Management Science, 2022)
This paper proposes a new seven level inverter with a solar power generation system, which is composed of a dc-dc power converter and a new seven level inverter. The dc-dc power converter integrates a boost converter and a transformer to convert the output voltage of the solar cell array into independent voltage sources with multiple relationships. The most commonly used solar cell model is introduced and the generalized PV model using Mat lab/simulink is developed. Taking the effect of solar intensity and cell temperature, the characteristics of PV model are simulated. This model can be used for analysis of PV characteristics and for simulation with Maximum power point tracking algorithms. This new seven level inverter is configured using a capacitor selection circuit and a full bridge power converter. The capacitor selection circuit converts the two output voltage sources of dc–dc power converter into a three-level dc voltage, and the full-bridge power converter further converts this three-level dc voltage into a seven-level ac voltage. In this way, the proposed solar power generation system generates a sinusoidal output current that is in phase with the utility voltage and is fed into the utility. The salient features of the proposed seven-level inverter are that only six power electronic switches are used, and only one power electronic switch is switched at high frequency at any time.